Evaluation of the effectiveness of mindfulness training on high-risk and procrastination behaviors and fear of success among students - Joghataei, Atefeh; Mafakheri, Abdollah; Bakhshipoor, Abolfazl (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to investigate the effect of mindfulness interventions on high-risk behaviors and procrastination and fear of students' success. Method: The method of this research is quasi-experimental pre-test and post-test with a control group. The statistical population consists of female high school students in the city of Jaghtai in the academic year 2021-22. The study sample was 30 people. Among the students, 30 people were selected by available sampling and then 15 people were randomly assigned to the experimental group and 15 people to the control group. Then the academic procrastination questionnaires of Solomon and Roth Blum (1984), fear of Zuckerman and Allison success (1979) and Mohammadkhani high risk behaviors questionnaire (2016) were given to the statistical sample. After the training sessions of Segal et al. (2002) mindfulness for the experimental groups, post-test was performed. The collected data were analyzed using repeated measures analysis of variance and SPSS software. Analysis of variance with repeated measures and SPSS software were used to analyze the data. Results: The results showed that mindfulness training on high-risk behaviors (F=78.35, p